Research on the Differential Model-Free Adaptive Mooring Control Method for Uncrewed Wave Gliders - Jian Shi; Jiangning Xu; Tianyu Wei; Yulei Liao; Kaiwen Pan; Min Jiang; Xiao Wu (Journal of Marine Science and Engineering)
Uncrewed Wave Gliders (UWGs) are capable of harnessing energy from ocean waves and photovoltaic sources to enable long-duration voyages. Since the float’s yaw motion relies on the rudder of the submersible for control, this introduces many unknown nonlinear and time-delay factors into the control system. Moreover, the susceptibility of UWGs to waves influences results in limited maneuverability and necessitates energy efficiency considerations, complicating the task of following a designated path to a specific point for observations. To address these challenges, this paper first introduces a differential model-free adaptive control (DMFAC) approach for managing the float’s heading control, along with a proof of its stability. Furthermore, an improved attractive force line-of-sight (IAFLOS) guidance strategy for overall mooring control is proposed. The integration of the DMFAC heading controller and the IAFLOS strategy forms a comprehensive mooring control system, which is validated through simulation studies in typical maritime conditions. This control system ensures that, while considering energy conservation strategies, the distance between the wave glider and the mooring point remains within 20 m during mooring.